Proceedings of the 2006 20th Anniversary Conference on Computer Supported Cooperative Work 2006
DOI: 10.1145/1180875.1180922
|View full text |Cite
|
Sign up to set email alerts
|

Revisiting Whittaker & Sidner's "email overload" ten years later

Abstract: Ten years ago, Whittaker and Sidner [8] published research on email overload, coining a term that would drive a research area that continues today. We examine a sample of 600 mailboxes collected at a high-tech company to compare how users organize their email now to 1996. While inboxes are roughly the same size as in 1996, our population's email archives have grown tenfold. We see little evidence of distinct strategies for handling email; most of our users fall into a middle ground. There remains a need for fu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
81
0
1

Year Published

2010
2010
2017
2017

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 106 publications
(85 citation statements)
references
References 6 publications
3
81
0
1
Order By: Relevance
“…The collections we used are equivalent in size to typical email collections [30,13]. However, collections can be much bigger [18]. It is important that automated experiments reflect this.…”
Section: Limitations and Discussionmentioning
confidence: 99%
“…The collections we used are equivalent in size to typical email collections [30,13]. However, collections can be much bigger [18]. It is important that automated experiments reflect this.…”
Section: Limitations and Discussionmentioning
confidence: 99%
“…A further limitation of email research to date is that it has concentrated on defining email practices for specific devices such as desktop computers, e.g. [10,33], or briefly outlining new uses of mobile phones with regard to emails, e.g. [20,23], but little research has compared email processing strategies on different devices or how they might result in work interfering with home life.…”
Section: Introductionmentioning
confidence: 99%
“…The same methodology as in [1] was used 10 years later by other authors in a paper [2] that revisited the email overload problem by analyzing a new email dataset from a technological company. It was found that some metrics, e.g.…”
Section: A Theoretical and Psychological Researchmentioning
confidence: 99%